Different effects of CYP27A1 and CYP7B1 on cognitive function: Two mouse models in comparison - Goikolea, Julen; Latorre-Leal, Maria; Tsagkogianni, Christina; Pikkupeura, Sonja; Gulyas, Balazs; Cedazo-Minguez, Angel; Loera-Valencia, Raul; Björkhem, Ingemar; Rodriguez Rodriguez, Patricia; Maioli, Silvia (The Journal of steroid biochemistry and molecular biology, 2023)
The oxysterol 27-hydroxycholesterol (27OHC) is produced by the enzyme sterol 27-hydroxylase (Cyp27A1) and is mainly catabolized to 7α-Hydroxy-3-oxo-4-cholestenoic acid (7-HOCA) by the enzyme cytochrome P-450 oxysterol 7α-hydroxylase (Cyp7B1). 27OHC is mostly produced in the liver and can reach the brain by crossing the blood-brain barrier. A large body of evidence shows that CYP27A1 overexpression and high levels of 27OHC have a detrimental effect on the brain, causing cognitive and synaptic dysfunction together with a decrease in glucose uptake in mice. In this work, we analyzed two mouse models with high levels of 27OHC: Cyp7B1 knock-out mice and CYP27A1 overexpressing mice. Despite the accumulation of 27OHC in both models, Cyp7B1 knock-out mice maintained intact learning and memory capacities, neuronal morphology, and brain glucose uptake over time. Neurons treated with the Cyp7B1 metabolite 7-HOCA did not show changes in synaptic genes and 27OHC-treated Cyp7B1 knock-out neurons could not counteract 27OHC detrimental effects. This suggests that 7-HOCA and Cyp7B1 deletion in neurons do not mediate the neuroprotective effects observed in Cyp7B1 knock-out animals. RNA-seq of neuronal nuclei sorted from Cyp7B1 knock-out brains revealed upregulation of genes likely to confer neuroprotection to these animals. Differently from Cyp7B1 knock-out mice, transcriptomic data from CYP27A1 overexpressing neurons showed significant downregulation of genes associated with synaptic function and several metabolic processes. Our results suggest that the differences observed in the two models may be mediated by the higher levels of Cyp7B1 substrates such as 25-hydroxycholesterol and 3β-Adiol in the knock-out mice and that CYP27A1 overexpressing mice may be a more suitable model for studying 27-OHC-specific signaling. We believe that future studies on Cyp7B1 and Cyp27A1 will contribute to a better understanding of the pathogenic mechanisms of neurodegenerative diseases like Alzheimer’s disease and may lead to potential new therapeutic approaches. •Cyp7B1 knock-out mice do not show cognitive and synaptic dysfunction, despite their high levels of 27-hydroxycholesterol.•In vitro treatments with Cyp7B1 metabolite 7-HOCA as well as Cyp7B1 silencing did not affect synaptic markers in neurons.•Transcriptomics data obtained from sorted cortical neuron nuclei from Cyp27Tg and CYP7B1KO mice reveal two distinct expression profiles.•Neurons from Cyp27Tg show significant downregulation of synaptic function and plasticity while Cyp7B1 knock-out primary neurons show upregulation of genes related to synaptic assembly, GABA-ergic signaling, and neuronal projection development.